Respons Pertumbuhan Bibit Budset Tebu (Saccharum officinarum L.) Varietas VMC 86-550 pada Beberapa Konsentrasi dan Frekuensi Aplikasi Pupuk Organik Cair (POC) Urine Sapi - Asmono, Sepdian Luri; Ramadhani, Wahyuning Putri (Jurnal Agro Industri Perkebunan, 2023)
Sugarcane (Saccharum officinarum L.) is an important plantation commodity as the main raw material for producing sugar consumed in Indonesia. One of the varieties cultivated is VMC 86-550, but one of the technical obstacles to its cultivation is the slow and non-uniform growth of the seeds. Therefore, one effort to maximize the growth of budset seed varieties requires proper nutrition and contains growth-promoting hormones. Therefore, this study aims to determine the response of giving liquid organic fertilizer (LOF) from cow urine to the growth of VMC 86-550 sugarcane seedlings using the budset method. To find out the purpose, this study used a factorial randomized block design with a concentration factor of LOF of cow urine consisting of five levels (0%, 10%, 15%, 20%, and 25%). The second factor is the application frequency which consists of once every 2 weeks and once every 4 weeks, so there were 10 treatments and repeated three times. This study used a completely randomized factorial design and was analyzed using ANOVA if there was a significant influence followed by Duncan Multiple Range Test (DMRT) at a 5% level using SPSS 20 software. Observation variables included plant height, stem diameter, number of leaves, number of tillers, and root length of sugarcane seedlings up to 90 HST. The results showed that the addition of cow urine LOF had an effect on the growth of sugarcane seedlings, both from the concentration and frequency of application, but the combination of the two did not have a significant effect on all observation variables.